Explorando a justiça organizacional, burnout e saúde nos servidores da UFSM - Schuster, Marcelo da Silva (2013)
The transformation of the organizational environment in recent decades, have directly impacted employees, their perceptions about the distribution of resources or tasks or how they are treated during this process can create stress in the workplace. When this stress occurs in a prolonged and chronic, can lead to emotional exhaustion of workers, which can generate forms of shutdown of the site and the people you work with, often resulting in various health problems. Such problems are perceived as indicators absenteeism, withdrawal for health care, personal conflicts, etc.., Resulting in loss of productivity for the organization. Thus, this study aims to answer the following research question: What is the impact of organizational justice and Burnout levels in the health of the public servant UFSM? For this we used descriptive study method, a quantitative approach to data collection through structured questionnaire based on validated instruments related to Burnout (Maslach, 1996, 2003) and Organizational Justice (Colquitt, 2001). The sample consisted of 511 participants, 57.3% female and 42.7% male, 63% of those in positions of administrative, 23.6% related to health and 13.4% are linked to teaching . It was evident that the servers have moderate levels of Burnout (1.5), and the female who has the highest rates of Burnout in the institution, Perceived Organizational Justice also found in the average level (3.91), even compared to organizational justice differences were found between the manning of the servers, who works with the Dean has linked lower average. With respect to the study hypotheses, H1: Organizational Justice positive impact on perceived health; H2: The level of Burnout negatively influence the perceived health of the servers; H3: The greater the Organizational Justice Minor Level of Burnout in Servers, all were confirmed, through tests of correlation and regression. Is possible to conclude that with the increase in organizational justice perception levels of Burnout on servers UFSM decrease by 26.7%. When the Burnout level servers increase their health perception decreases in the proportion of 8% and when the perceived Organizational Justice increases the perceived health of servers increases to a level of 5%. As a suggestion is the development of training and interpersonal relationships to all servers, especially those who are in management positions, to address aspects of interactional justice, in addition to the completion of scaling in the university to address aspects of procedural and distributive justice.